Non-Olympic sport as a social institution at the level of statehood - Nina Dolbysheva (Слобожанський науково-спортивний вісник, 2015)
Purpose: to identify and disclose the particular social institution of non-Olympic sports. Material and Methods: to determine the goal axiomatic method used and the method of system analysis at the theoretical level. Results: the structure and activities of non-Olympic sport social institution at the level of state, which includes: social norms, rules and laws; specialized agencies and institutions; community organizations; system of training; social control are presented. The features of the functions of a social institution of non-Olympic sport, such as: relational, regulatory, political and ideological, integrative, transpirant, communicative ones. Conclusion: non-Olympic sport in Ukraine has emerged as a social institution that has its autonomy, is subordinated to social laws and performs certain functions.